Effect of oral contraceptive with and without associated estriol on ultrasound measurements of breast fibroadenoma: randomized clinical trial - Estevão, Rodrigo Augusto Fernandes; Nazário, Afonso Celso Pinto; Baracat, Edmund Chada (São Paulo Medical Journal, 2007)
CONTEXT AND OBJECTIVE: Fibroadenomas are the most common benign tumors of the female breast. The aim of this study was to evaluate the proliferative activity of breast fi broadenoma as shown by ultrasound measurements, following administration of oral contraceptives with and without associated estriol. DESIGN AND SETTING: This was a randomized, double-blind, placebo-controlled clinical trial carried out in the Mastology Sector, Department of Gynecology, Universidade Federal de São Paulo. METHODS: We studied 33 women with fi broadenomas. Ten were placed in group 1 and took an oral contraceptive consisting of levonorgestrel and ethinyl estradiol together with placebo material in the same capsule, for four consecutive cycles with a seven-day interval between them. The other 23 patients constituted group 2 and took the oral contraceptive as above together with estriol in the same capsule, in the same way as done by the group 1 patients. We took ultrasound measurements of their tumors (in three dimensions) before and after the intake of medication. At the end of the study, all the patients had their tumors removed by surgery. RESULTS: We observed decreased fibroadenoma width among the users of oral contraceptives with placebo, and this decrease was statistically signifi cant. In the other group, we did not observe any changes (in width, length or height). CONCLUSION: The results confi rm that estriol may block the protective effect of oral contraceptives on fi broadenomas, since we observed decreased fi broadenoma width among the group 1 patients but not the group 2 patients.